The Multivariate Differences of Key Factors in Early Childhood Teacher Professional Development in Shandong Province - Xie, Shuxin; Boonphadung, Suttipong (Journal of Cultural Analysis and Social Change, 2025)
As China’s preschool education system transitions from scale expansion to quality-oriented development, teachers’ professional competence has become a critical determinant of educational quality. However, empirical evidence remains limited regarding how organizational and individual factors differentially influence teachers’ professional knowledge, teaching behavior, and instructional innovation. This study employed a quantitative research design using stratified random sampling. Data were collected through a questionnaire survey administered to 500 in-service preschool teachers in Linyi, Weifang, and Jining, Shandong Province, China. Four independent variables—teacher educational qualifications, quarterly training frequency, kindergarten size, and directors’ leadership styles—were examined. Teachers’ professional competence was operationalized across three dimensions: professional knowledge, teaching behavior, and instructional innovation. Multivariate analysis of variance (MANOVA) was applied to test the differential effects of the independent variables on the dependent constructs. The results indicate that quarterly training frequency is the most influential and comprehensive predictor of preschool teachers’ professional competence, demonstrating significant positive effects across all three dimensions. Directors’ transformational leadership style significantly outperforms transactional and servant leadership in enhancing teachers’ professional knowledge depth, optimizing interactive teaching behaviors, and stimulating instructional innovation. Teachers’ educational qualifications significantly predict professional knowledge accumulation and innovation potential but do not exert a statistically significant effect on routine teaching behaviors. Kindergarten size shows no significant impact on any dimension of teachers’ professional competence. The findings highlight the pivotal role of organizational “soft power,” particularly systematic professional training and transformational leadership, in fostering preschool teachers’ professional development. Compared with structural or scale-based investments, capacity-building mechanisms generate substantially greater returns for improving educational quality. These results provide empirical support for policy and management strategies that prioritize professional learning systems and leadership development to advance high-quality preschool education in China.